Perspectives concerning leadership research in the framework of corporate sustainability - Gorski, Andra-Teodora; Ranf, Diana Elena; Badea, Dorel; Halmaghi, Elisabeta-Emilia; Gorski, Hortensia (Journal of Business Economics and Management, 2025)
The main purpose of this paper is to explore current perspectives on the approach to the concept of leadership in relation to sustainability. The research question is focused on the importance of leadership and its contribution as a driver of change, in the organizational sustainability context. The methodology of research has as main framework the bibliometric analysis approach. This quantitative research method allowed achieving some specific objectives, such as: determining the scientific interest in the studied topic and the main authors in the field, identifying the key concepts that interfered with leadership and sustainability and highlighting the main leadership style that facilitates the transition to sustainability. It is thus intended to make a valuable and up-to-date contribution to 2024 on the main trends manifested in leadership research as theory and practice. Among the main findings obtained, it is highlighted that, after 2020, the top three leadership styles that have created links in correlation with other concepts, thus generating organizational change, are: transformational leadership, ethical leadership and authentic leadership. Of these, transformational leadership stands out as a key factor in driving innovation and sustainable performance, this fact being valuable to managers and researchers.